2012
DOI: 10.4317/medoral.17576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sociodemographic factors upon pain intensity in patients with temporomandibular joint disorders seen in the primary care setting

Abstract: Objective: A study is made of the influence of gender, educational level, marital status, income, social support, and perceived general and oral health upon pain intensity in a sample of patients with temporomandibular joint disorders (TMJD) explored in primary care (AP). Design: A review was made of 899 patients from Córdoba Healthcare District (Spain) referred to the primary care TMJD Unit by their primary care physician and/or dentist. Of these subjects, 151 failed to meet the inclusion criteria. The remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
6
16
1
4
Order By: Relevance
“…Hungria et al, in relation to temporomandibolar disorders (TMD) found that patients with a lower educational level suffer more from pain than people with a higher educational level. However, in our patients pain was not related to educational level (P = 0.288) [41].…”
Section: Discussioncontrasting
confidence: 70%
“…Hungria et al, in relation to temporomandibolar disorders (TMD) found that patients with a lower educational level suffer more from pain than people with a higher educational level. However, in our patients pain was not related to educational level (P = 0.288) [41].…”
Section: Discussioncontrasting
confidence: 70%
“…Some studies have shown that prevalence of TMD in elderly populations is rare (15)(16)(17) . However, other authors reported that the elderly can often suffer from TMD, but do not complain because they are more concerned with other overall health issues or more painful and debilitating diseases, leaving aside the symptoms related to the masticatory system (18) .…”
Section: Discussionmentioning
confidence: 99%
“…This condition is often diagnosed by observation of symptoms that are very subjective. Identification of these symptoms depends on cognitive ability, which varies widely both individually and among groups (15)(16)(17)(18) . According to Schmitter et al (18) , the elderly population presents a higher prevalence of objective signs of TMD; however, they rarely complain of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently pain related complains (neck, head, TMJ) will be one of the most important and prevalent problem in persons with TMJD. In this aspect woman seems to have higher and more severe pain prevalence [6,[8][9][10]. Psychological abnormalities have been also associated with elevated pain grade [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect woman seems to have higher and more severe pain prevalence [6,[8][9][10]. Psychological abnormalities have been also associated with elevated pain grade [8,9,11]. In this context, though most of TMJ patients will remain asymptomatic or have symptoms during a short time [1,12] pain relief will be one of the main goals of TMJD treatment.…”
Section: Introductionmentioning
confidence: 99%